A CCL1/CCR8-dependent feed-forward mechanism drives ILC2 functions in type 2-mediated inflammation - Knipfer, Lisa; Schulz-Kuhnt, Anja; Kindermann, Markus; Greif, Vicky; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, Imke; Wirtz, Stefan (Journal of Experimental Medicine, 2019)
Group 2 innate lymphoid cells (ILC2s) possess indispensable roles during type 2-mediated inflammatory diseases. Although their physiological and detrimental immune functions seem to depend on the anatomical compartment they reside, their tissue tropism and the molecular and immunological processes regulating the self-renewal of the local pool of ILC2s in the context of inflammation or infection are incompletely understood. Here, we analyzed the role of the CC-chemokine receptor CCR8 for the biological functions of ILC2s. In vitro and in vivo experiments indicated that CCR8 is in comparison to the related molecule CCR4 less important for migration of these cells. However, we found that activated mouse and human ILC2s produce the CCR8 ligand CCL1 and are a major source of CCL1 in vivo. CCL1 signaling to ILC2s regulates their proliferation and supports their capacity to protect against helminthic infections. In summary, we identify a novel chemokine receptor-dependent mechanism by which ILC2s are regulated during type 2 responses.
CRIS-Team Scopus Importer:2019-12-13

Affected differentiation and function of innate lymphoid cells type 2 in the absence of the Th2-and Th1-associated transcription factor NIP45 - Koch, Sonja; Springel, R.; Knipfer, Lisa; Wirtz, Stefan; Finotto, Susetta (2018)
EVALuna2:207770

An in vivo gene delivery approach for the isolation of reasonable numbers of type 2 innate lymphoid cells - Frech, Michael; Knipfer, Lisa; Wirtz, Stefan; Zaiss, Mario (MethodsX, 2020)
Group 2 innate lymphoid cells (ILC2s) are a recently recognized subset of innate lymphocytes with crucial role in mucosal immunity and tissue homeostasis. Over the past decade, substantial advances in our understanding of ILC2 biology have established them as an essential element in innate and adaptive immunity. However, their relatively low abundance and laborious purification from mucosal tissues make their study difficult. Moreover, due to a lack of an ILC2-specific Cre mouse-line, adoptive transfer of ILC2s into ILC-deficient hosts is inevitable. Herein we describe an in-depth protocol for the induction, isolation, and expansion of murine ILC2s. By combining an in vivo gene delivery approach to boost ILC2 numbers and a cell culture strategy to expand isolated cells, large quantities of highly pure ILC2s can be obtained. The isolated cells maintain their phenotype and can be used for subsequent cell transfer or in vitro studies. In comparison to previous protocols, this approach is cost-effective and efficient with potential yield of more than 20 million ILC2s isolated per mouse. • Group 2 innate lymphoid cells (ILC2s) are extensively studied in mouse models and humans in recent years. • Low abundance of ILC2s and current lack of specific ILC2 knockout mice makes in vivo research challenging. • This method allows high and pure ILC2 numbers for in vitro or adoptive in vivo transfer experiments.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Cell culture; Cytokines; Fluorescent activated cell sorting; Group 2 innate lymphoid cells; Isolation and expansion of murine ILC2s

Ethanol consumption inhibits TFH cell responses and the development of autoimmune arthritis - Azizov, Vugar; Dietel, Katharina; Steffen, Franziska; Dürholz, Kerstin; Meidenbauer, Julia; Lucas, Sébastien; Frech, Michael; Omata, Yasunori; Tajik, Narges; Knipfer, Lisa; Kolenbrander, Anne; Seubert, Silvia; et al. (Nature Communications, 2020)
Alcohol consumption is a consistent protective factor for the development of autoimmune diseases such as rheumatoid arthritis (RA). The underlying mechanism for this tolerance-inducing effect of alcohol, however, is unknown. Here we show that alcohol and its metabolite acetate alter the functional state of T follicular helper (TFH) cells in vitro and in vivo, thereby exerting immune regulatory and tolerance-inducing properties. Alcohol-exposed mice have reduced Bcl6 and PD-1 expression as well as IL-21 production by TFH cells, preventing proper spatial organization of TFH cells to form TFH:B cell conjugates in germinal centers. This effect is associated with impaired autoantibody formation, and mitigates experimental autoimmune arthritis. By contrast, T cell independent immune responses and passive models of arthritis are not affected by alcohol exposure. These data clarify the immune regulatory and tolerance-inducing effect of alcohol consumption.
CRIS-Team Scopus Importer:2020-05-05

Group 2 Innate Lymphoid Cells (ILC2) Suppress Beneficial Type 1 Immune Responses During Pulmonary Cryptococcosis - Kindermann, Markus; Knipfer, Lisa; Obermeyer, Stephanie; Müller, Uwe; Alber, Gottfried; Bogdan, Christian; Schleicher, Ulrike; Neurath, Markus; Wirtz, Stefan (Frontiers in Immunology, 2020)
Cryptococcus neoformans is an opportunistic fungal pathogen preferentially causing disease in immunocompromised individuals such as organ-transplant-recipients, patients receiving immunosuppressive medications or, in particular, individuals suffering from HIV infection. Numerous studies clearly indicated that the control of C. neoformans infections is strongly dependent on a prototypic type 1 immune response and classical macrophage activation, whereas type 2-biased immunity and alternative activation of macrophages has been rather implicated in disease progression and detrimental outcomes. However, little is known about regulatory pathways modulating and balancing immune responses during early phases of pulmonary cryptococcosis. Here, we analyzed the role of group 2 innate lymphoid cells (ILC2s) for the control of C. neoformans infection. Using an intranasal infection model with a highly virulent C. neoformans strain, we found that ILC2 numbers were strongly increased in C. neoformans-infected lungs along with induction of a type 2 response. Mice lacking ILC2s due to conditional deficiency of the transcription factor RAR-related orphan receptor alpha (Rora) displayed a massive downregulation of features of type 2 immunity as reflected by reduced levels of the type 2 signature cytokines IL-4, IL-5, and IL-13 at 14 days post-infection. Moreover, ILC2 deficiency was accompanied with increased type 1 immunity and classical macrophage activation, while the pulmonary numbers of eosinophils and alternatively activated macrophages were reduced in these mice. Importantly, this shift in pulmonary macrophage polarization in ILC2-deficient mice correlated with improved fungal control and prolonged survival of infected mice. Conversely, adoptive transfer of ILC2s was associated with a type 2 bias associated with less efficient anti-fungal immunity in lungs of recipient mice. Collectively, our date indicate a non-redundant role of ILC2 in orchestrating myeloid anti-cryptococcal immune responses toward a disease exacerbating phenotype.
CRIS-Team Scopus Importer:2020-03-10
Keywords: fungi (Candida; Cryptococcus); ILC2; innate immunity; lung infection; type 2 immune response

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

ILC2s in infectious diseases and organ-specific fibrosis - Kindermann, Markus; Knipfer, Lisa; Atreya, Imke; Wirtz, Stefan (Seminars in Immunopathology, 2018)
Type 2 immune responses evolved to provide host protection against parasitic infections and to support the repair of infection-induced tissue injury. However, persistent chronic organ damage can result in dysregulated production of critical type 2 cytokines supporting tissue remodeling and fibrosis development. Recently, group 2 innate lymphoid cells (ILC2s) were newly described as central innate mediators of type 2 responses. In particular, by secretion of the cytokines IL-5, IL-9, and IL-13 and the growth factor amphiregulin in response to the release of tissue-derived alarmins, ILC2s have been shown to substantially contribute to both the dismissal of metazoan parasites and the repair of infection-dependent or sterile tissue damage. Conversely, cytokine production by ILC2s emerged as a driving force for tissue remodeling and excessive fibrosis in several organ systems including the lung, liver, and skin. In this review, we discuss how ILC2s are specifically implicated in the body's immune response to different pathogenic infections and how dysregulated ILC2s may promote organ-specific fibrosis.
EVALuna2:35153

Immunoregulatory role of NFAT-interacting protein (NIP) 45 in adaptive and innate immune responses in allergic asthma - Koch, Sonja; Maeding, N.; Karwot, R.; Mirzakhani, H.; Springel, R.; Mittler, S.; Zimmermann, Theodor; Melichar, V. O.; Knipfer, Lisa; Wirtz, Stefan; Weiss, S. T. (2017)
EVALuna2:33897

Targeted deletion of NFAT-Interacting-Protein-(NIP) 45 resolves experimental asthma by inhibiting Innate Lymphoid Cells group 2 (ILC2) - Koch, Sonja; Knipfer, Lisa; Kölle, Julia; Mirzakhani, Hooman; Graser, Anna; Zimmermann, Theodor; Kiefer, Alexander; Melichar, Volker O.; Rascher, Wolfgang; Papadopoulos, Nikolaos G.; Rieker, Ralf; Raby, Benjamin A.; et al. (Scientific Reports, 2019)
Here we investigated the role of NFAT-interacting protein (NIP)-45, an Interleukin (IL)-4 inducing Transcription Factor, and its impact on the differentiation of Group 2 Innate -Lymphoid -Cells (ILC2s) in the pathogenesis of asthma. NIP45, a transcription factor regulating NFATc1 activity, mRNA was found to be induced in the Peripheral Blood mononuclear cells (PMBCs) of asthmatic pre-school children with allergies and in the peripheral blood CD4+ T cells from adult asthmatic patients. In PBMCs of asthmatic and control children, NIP45 mRNA directly correlated with NFATc1 but not with T-bet. Targeted deletion of NIP45 in mice resulted in a protective phenotype in experimental asthma with reduced airway mucus production, airway hyperresponsiveness and eosinophils. This phenotype was reversed by intranasal delivery of recombinant r-IL-33. Consistently, ILC2s and not GATA3+ CD4+ T-cells were decreased in the lungs of asthmatic NIP45−/− mice. Reduced cell number spleen ILC2s could be differentiated from NIP45−/− as compared to wild-type mice after in vivo injection of a microcircle-DNA vector expressing IL-25 and decreased cytokines and ILC2 markers in ILC2 differentiated from the bone marrow of NIP45−/− mice. NIP45 thus emerges as a new therapeutic target for the resolution of the airway pathology, down-regulation of ILC2s and mucus production in asthma.
CRIS-Team Scopus Importer:2019-11-08

Targeting of the Tec Kinase ITK Drives Resolution of T Cell–Mediated Colitis and Emerges as Potential Therapeutic Option in Ulcerative Colitis - Lechner-Grimm, Kristina; Mott, Stefanie; Al-Saifi, Ragheed; Knipfer, Lisa; Wirtz, Stefan; Atreya, Raja; Vieth, Michael; Rath, Timo; Fraass, Tina; Winter, Zoltan; August, Avery; Luban, Jeremy; et al. (Gastroenterology, 2021)
Background & Aims: The molecular checkpoints driving T cell activation and cytokine responses in ulcerative colitis (UC) are incompletely understood. Here, we studied the Tec kinase ITK in UC. Methods: We analyzed patients with inflammatory bowel disease (n = 223) and evaluated ITK activity as well as the functional effects of cyclosporine-A (CsA). In addition, 3 independent murine colitis models were used to investigate the functional role of ITK. Finally, the activity of ITK was blocked via pharmacological inhibitors and genetically engineered mice. Readout parameters were mini-endoscopy, histopathology, mucosal T cell apoptosis, and cytokine production. Results: We found an expansion of pITK-expressing mucosal CD4+ T cells in UC rather than Crohn's disease that correlated with disease severity. CsA suppressed activation of ITK in cultured CD4+ T cells and calcineurin-containing microclusters adjacent to the T cell receptor signaling complex. Functionally, the capacity of CsA to suppress activity of experimental colitis was critically dependent on ITK. Genetic inactivation of Itk via gene targeting or induction of allele-sensitive Itk mutants prevented experimental colitis in 3 colitis models, and treatment with pharmacological ITK blockers suppressed established colitis. In addition, ITK controlled apoptosis and activation of mucosal Th2 and Th17 lymphocytes via NFATc2 signaling pathways. Conclusions: ITK activation was detected in UC and could be down-regulated in cultured T cells by CsA administration. Selective targeting of ITK emerges as an attractive approach for treatment of chronic intestinal inflammation and potentially UC by driving resolution of mucosal inflammation.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Cyclosporine A; Cytokines; IBD; ITK; Therapeutic Strategies

The role of Krueppel-like factor 2 in B cell activation and plasma cell homeostasis - Schubert, T.; Knipfer, Lisa; Wallrapp, Antonia; Wittner, Jens; Jäck, Hans-Martin; Schuh, Wolfgang (2017)
EVALuna2:13652

The role of the chemokine receptor CCR8 in migration and effector function of innate lymphoid cells type 2 - Knipfer, Lisa; Schulz-Kuhnt, Anja; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, I.; Wirtz, Stefan (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Type 2 innate lymphoid cells inhibit the differentiation of osteoclasts and protect from ovariectomy-induced bone loss - Omata, Yasunori; Frech, Michael; Lucas, Sébastien; Primbs, Tatjana; Knipfer, Lisa; Wirtz, Stefan; Kadono, Yuho; Saito, Taku; Tanaka, Sakae; Sarter, Kerstin; Schett, Georg; Zaiss, Mario (Bone, 2020)
While the role of T cells in the regulation of bone homeostasis is well defined, little is known about the role of innate lymphoid cells (ILCs) on bone. ILCs are innate immune cells that share cytokine expression patterns with T cells but lack the T cell receptor. In this study we show that type 2 ILCs (ILC2) potently inhibit the generation of bone resorbing osteoclasts in vitro as well as favorably influence bone homeostasis under steady state conditions in vivo using loss and gain of function models. Furthermore, adoptive transfer of ILC2 completely abrogated ovariectomy-induced bone loss by significantly down-regulating osteoclast numbers in vivo. The suppressive effects of ILC2s on osteoclasts in vitro and in vivo as well as the protection from ovariectomy-induced bone loss were linked to their expression of IL-4 and IL-13 as well as STAT6 activation on the myeloid target cell, since deletion of IL-4/IL-13 in ILC2s or STAT6 in osteoclast precursors abrogated the anti-osteoclastogenic effect of ILC2s. Taken together, these findings show that ILC2 have to be considered as potent regulators of bone homeostasis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Bone loss; Cytokines; ILC2; Osteoclasts; Osteoimmunology; Type 2 innate lymphoid cells type